Djibouti : Poverty Reduction Strategy Paper: Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2012)
The modern economy of the Republic of Djibouti is based on rents directly or indirectly originating from the international port of Djibouti and from the country's strategic position. The Poverty Reduction Strategy Paper discusses that the growth recorded over the last five years is essentially driven by the increase in foreign direct investment-but especially by the activities of the Port of Djibouti. The informal economy constitutes a major proportion of the economic activities of Djibouti and provides a livelihood for much of the Djibouti population.